PROFESSIONAL SELF-IMPROVEMENT OF SOCIAL EDUCATORS IN VOCATIONAL EDUCATION INSTITUTIONS (Innovative professional education, 2023)
The article analyzes the peculiarities of professional self-improvement of a social pedagogue in vocational education institutions. The relevance of this problem is due to the awareness of specialists of the urgent need for constant deepening and expansion of the acquired knowledge, skills and abilities for the successful completion of tasks within the framework of professional activity, development of creative potential for solving problem situations in professional work, their persistent desire for self-improvement and self-realization. The essential characteristics and key mechanisms of professional self-improvement of pedagogical workers under martial law, which is manifested in the improvement of professional competencies, are determined. The effective ways of professional self-improvement of social pedagogues include self-educational activities in the intercourse period of advanced training. Effective mechanisms of this process are the activation of personal potential and its rational use in the design of professional self-development.
Keywords: professional education, professional self-improvement, social pedagogue, professionalism